New TRAP1 and Hsp90 chaperone inhibitors with cationic components: Preliminary studies on mitochondrial targeting. Issue 13 (15th July 2018) - Rondanin, R.; Lettini, G.; Oliva, P.; Baruchello, R.; Costantini, C.; Trapella, C.; Simoni, D.; Bernardi, T.; Sisinni, L.; Pietrafesa, M.; Ponterini, G.; Costi, M.P.; et al.
Graphical abstract: Highlights: Analogues of known Hsp90 inhibitors with a permanent or ionizable cationic head. Inhibition of TRAP1 ATPase activity and detection in mitochondrial cell fraction. Best apoptotic and growth inhibition activities of guanidine bearing derivative. Similar affinities of most active compound for Hsp90 and TRAP1 binding. Abstract: TRAP1 (Hsp75) is the mitochondrial paralog of the Hsp90 molecular chaperone family. Due to structural similarity among Hsp90 chaperones, a potential strategy to induce apoptosis through mitochondrial TRAP1 ATPase inhibition has been envisaged and a series of compounds has been developed by binding the simple pharmacophoric core of known Hsp90 inhibitors with various appendages bearing a permanent cationic head, or a basic group highly ionizable at physiologic pH. Cationic appendages were selected as vehicles to deliver drugs to mitochondria. Indeed, masses of new derivatives were evidenced to accumulate in the mitochondrial fraction from colon carcinoma cells and a compound in the series, with a guanidine appendage, demonstrated good activity in inhibiting recombinant TRAP1 ATPase and cell growth and in inducing apoptotic cell death in colon carcinoma cells.